Gene expression analysis in mastocytosis reveals a highly consistent profile with candidate molecular markers - D'Ambrosio, Claudio; Akin, Cem; Wu, Yalin; Magnusson, Magnus K; Metcalfe, Dean D (Journal of allergy and clinical immunology, 2003)
Mastocytosis is a rare clonal disorder that might be accompanied by non-mast-cell clonal hematologic disorders, such as myeloproliferative or myelodysplastic syndromes. Our aim was to further understand the pathologic basis of mastocytosis and to identify novel molecular markers of disease. Microarray analysis was performed on RNA preparations obtained from bone marrow mononuclear cells of patients with mastocytosis. Results were compared with gene expression profiles performed on bone marrow mononuclear cells of healthy subjects. Analysis of gene expression in neoplastic bone marrow tissues revealed highly consistent profiles. One hundred four genes were significantly upregulated, and 64 genes were significantly downregulated in the bone marrow of patients with mastocytosis. The most prominent differentially expressed gene was α-tryptase (44.6-fold increase). Also upregulated were genes involved in cell proliferation, neoplastic transformation, and apoptosis. Both hierarchical and K-means clustering analyses identified an identical group of 10 genes highly coordinately overexpressed in patients with mastocytosis, including genes for the mast-cell-associated enzymes α- and β-tryptase and carboxypeptidase A. The expression level of 3 of these 10 genes (α-tryptase, the activating transcription factor type 3, and the muscle aponeurotic fibrosarcoma type F oncogene) was significantly correlated with serum tryptase levels, a surrogate marker of disease. The data presented in this study reveal significant differences in gene expression in the bone marrow of patients with mastocytosis compared with healthy subjects, demonstrate highly coordinated genes that might contribute to pathology, and identify 3 genes as candidate molecular markers for systemic disease.